A study on the determinants of net interest margin in Public Bank Berhad / Naziha Rifhan Mat Ali - Mat Ali, Naziha Rifhan (Faculty of Business and Management, 2011)
This paper studies on determinants of bank net interest margin (NIM) of Public Bank Berhad from 2001 until 2010. Most study has follows the basic theoretical model of net interest margin proposed by Ho and Saunders (1981) and its extension proposed by Maudos and Guevara (2004). The scope of the study only focuses on determinants net interest margin which are average operating cost, loan ratio and inflation rate. The Multiple Linear Regression Model is use to investigate the relationship between net interest margin with the average operating cost, loan ration and inflation rate by using SPSS Software. According to the overall result in this study it indicates the most independent variables are the most give an impact to the net interest margin (NIM) is average operating cost (AOC). It shows a positive and significant relationship between NIM and AOC. While loan ratio has negative relationship and inflation rate has positive relationship but both don’t have a significance relationship with the NIM in Public Bank Berhad.